Determination of Factors for Giving Formula Milk to Babies Aged 0–6 Months in the Work Environment Primary Health Care Pujon - Dewy Supriyani; Widia Shofa Ilmiah (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Giving breast milk (ASI) exclusively during the first six months of a baby's life is very important in supporting the baby's growth and development and body resilience. However, the practice of giving formula milk is still quite high and is a challenge in fulfilling exclusive breastfeeding. This study aims to determine the determining factors for giving formula milk to babies aged 0-6 months in the work environment UPT Primary Health Care Pujon. This research design uses a descriptive analytical approach with a cross-sectional method to identify factors associated with exclusive breastfeeding. The research population was all mothers who had babies with a sample of 52 respondents obtained through total sampling. Data analysis was carried out using the Chi-Square test and logistic regression to determine the most dominant factors. The research results showed that all variables had a p value > 0.05, namely age (p=0.274), education (p=0.156), occupation (p=0.384), parity (p=0.280) and socio-culture (p=0.711), so there was no significant relationship between these variables and exclusive breastfeeding. The logistic regression model was also not significant (p=0.308), indicating that there were no dominant factors influencing the practice of exclusive breastfeeding among respondents. Thus, the low coverage of exclusive breastfeeding in this study may be influenced by other factors outside the variables studied.